The Effectiveness of Group Counseling With Cognitive Restructuring and Self-Management Techniques to Reduce Academic Procrastination - Elfida Putri, Mela; Eddy Wibowo, Mungin; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2021)
Academic procrastination truly disadvantages students’ learning achievement. Hence, interventions to reduce this procrastination rate becomes significant. To realize effort, the current study attempted to examine the effectiveness of group counseling with cognitive restructuring and self-management techniques to reduce students’ academic procrastination. This experimental study involved 24 students selected using purposive random sampling. For the instrument, questionnaire was used to collect the data of their academic procrastination, while two-way ANOVA was to perform the analysis. Based on the results, the group counseling with cognitive restructuring, self-management techniques, and their combination worked effectively to reduce academic procrastination. It was also found that the group counseling with the combination of both techniques performed better than the use of each technique separately. At last, this study was focused on combining cognitive restructuring and self-management techniques to reduce students’ academic procrastination